Penerapan Program Edukasi Dan Ketersediaan Alcohol Based Hand Rub (ABHR) Dalam Upaya Peningkatan Perilaku Patuh Hand Hygiene Perawat Di Rumah Sakit X - Nur Fitriah Efendy; Serri Hutahaean (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The purpose of this study is to identify compliance level of hand hygiene and also to analyze the effectiveness educational program and availability ABHR (alcohol based hand rub) can improve compliance hand hygiene among nurses in Hospital X.Methods: This research using quasi experiment without control group. Total of 30 respondents join this research which is all the nurses who work Hospital XResults: Before intervention it was found that 76,9% did not compliance with hand hygiene while 23,1% complied.  Then intervention of education program and the available of ABHR was carried out. Post test was conducted to determine the effectiveness of the intervention carried out. Post test results as many as 61.5% were obedient while 38.5% were not.Conclusion: It can be stated that giving intervention by educational program and availability ABHR can improve compliance hand hygiene among nurses.